THE EFFECT OF THE INTENSITY OF ACCESSING THE HOAX NEWS IN THE INSTAGRAM AND IN FACEBOOK RELATED TO COVID-19 ON THE LEVEL OF DISINFORMATION - Eirene widjajanto; Wahyu Kristian Natalia (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2021)
The spread of hoax news is currently rife, both only for viral, diversifying issues, or bringing someone down. Hoax news is often distributed and received in the form of writing, pictures, videos, and social media. One of the well-known social media services is Instagram and Facebook. Hoax news often appears on the internet and media such as Instagram and Facebook. Intensity of accessing news hoax related Covid- 19 on social media in 2020 can effect the level of disinformation public. The study aims to determine the effect of the intensity of accessing news hoax Instagram and Facebook related Covid- 19 the level of disinformation public. This type of research is a survey. The theory used is the Uses and Effect Theory. The data collection technique used a questionnaire. The data analysis technique used is descriptive statistics, simple linier regression analysis, and multiple linier regression analysis, and multiple linier regression analysis. The sampling technique used in this research was Probability Sampling. While the coefficient of determination is 0.098, wich means that the the intensity of accessing news hoax Instagram and Facebook related Covid- 19 level contributes to the level of disinformation public by 9,8% while the remaining 90,2% is influenced by variables outside of intensity access.